THE IMPORTANCE OF ENGLISH IN GLOBAL MARKET - Azimdjanova Farangiz; Nurova Maftuna (TADQIQOTLAR, 2025)
Introduction In today’s interconnected world, language plays a key role in international cooperation, trade, and communication. Among all global languages, English has emerged as the dominant medium in global markets. From multinational corporations to small exporters, English is essential for negotiating, marketing, and establishing global partnerships. This article explores why English holds such an influential position in international trade and how it contributes to business success worldwide.